Experiences of Students Enrolled in Integrated Collaborative College/University Programs - Landeen, Janet; Matthew-Maich, Nancy; Marshall, Leslie; Hagerman, Lisa-Anne; Bolan, Lindsay; Parzen, Maurine; Pavkovic, Maria; Riehl, Christine; Carvalho, Joshua; Bilau, Natasha; Zhang, Zetian; Oliver, Sheri; et al. (Canadian Journal of Higher Education, 2017)
Little is known about the student experience in collaborative college/university programs, where students are enrolled in two institutions simultaneously in integrated curriculum designs. This interpretive, descriptive, qualitative study explored these students’ perspectives. Sixty-eight participants enrolled in one of four collaborative programs from three different faculties engaged in student researcher-led focus groups. Results revealed that while all participants valued their respective academic programs, their day-to-day life experiences presented a different story. Some students had perceptions of belonging and thrived in a dual world. Others had perceptions of ambiguous belonging, which contributed to them perceiving themselves through a perpetual lens of being less than university-only students. Issues of how students are invited to engage in the university and college cultures, perceptions of power and control, and daily reminders of being different all contributed to positive or ambiguous student identities. The results raise preliminary questions for universities and colleges regarding how to enhance the student experience in these collaborative programs.